PENERAPAN TEORI BRUNNER DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR DI KELAS III SDN 002 BANTAYAN - Almahera, Almahera; Putra, Zetra Hainul; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This study is generally motivated by the mathematical learning result of the third grade students SDN 002 Bantayan that is still low, with an average grade 65.8. While the value of the minimum completeness criteria (KKM) is 70. Among 25 students, there are only 11 students reach KKM. This research is a classroom action research (PTK) that aims to improve students' mathematics learning outcomes of third grade students SDN 002 Bantayan with the application of the Brunner theory. Data collection instruments in this research are teacher’ and students’ activity sheets as well as learning outcomes. This research is obtained from an average score 65,8 before treatment increased to 81.2 in cycle I, and on the second cycle increased to 85.6. The activities of teachers in the first cycle of the first meeting obtains 78.8% with the enough category, at the second meeting increased to 82.6% with the good category. At the first meeting of the second cycle increased to 88.4% with the category is still good, while the latter is more increased to 92.3% with very good category. Activity of students in the first cycle the first meeting is enough category 79,1%, and in the second meeting increased 81.2%, with good category. At this cycle students begin to understand the learning using Brunner theory marked by students’ activites in the first meeting of second cycle increased to 87.5 &% good category, and the second meeting of the second cycle becoming 93.7% with very good category. Results of this study prove that the application of the Brunner theory can improve students' mathematical learning outcomes of grade III SDN 002 Bantayan.Keywords: Brunner Theory, Mathematics Learning Outcomes